Conventional Practice of use of Cotton Bud in External Auditory Canal and it’s Complications (Bangladesh Journal of Otorhinolaryngology, 2022)
Objectives: To find out the complications arise from use of cotton bud in external auditory canal.Methods: This cross sectional study was carried out from January 2020- December 2020 in Pabna medical college hospital. About 100 patients with complications of cotton bud use were included in this study. Diagnosis was based on the history and otoscopic examination.Results: In this study most of the cases were age group 0-10 years -30%, 10-50-years 30%, 50-60- years 10%, more than 60 years 40%. Common Complications were Infection of external auditory canal 50%, injury to external auditory canal 40% and injury to tympanic membrane 10%.Conclusion: Injudicious use of Cotton bud has injurious effect for external auditory canal and should be avoided.Bangladesh J Otorhinolaryngol 2022; 28(1): 91-95